Safety and Efficacy of Tirofiban Combined With Mechanical Thrombectomy Depend on Ischemic Stroke Etiology - Sun, Chao; Li, Xiang; Zhao, Zheng; Chen, Xiangliang; Huang, Chaoping; Li, Xuemei; Shan, Yajie; Zou, Yang; Liu, Yukai; Ibrahim, Mako; Nyame, Linda; Song, Baili; et al. (Frontiers in Neurology, 2019)
Background and Purpose: The clinical use of tirofiban for patients with acute ischemic stroke (AIS) who underwent mechanical thrombectomy (MT) remains controversial. We aimed to evaluate the safety and efficacy of tirofiban combined with MT in AIS patients. Methods: Patients with AIS who underwent MT from January 2014 to December 2018 were enrolled in three stroke units in China. Subgroup analyses were performed based on stroke etiology which was classified according to the Trial of ORG 10172 in Acute Stroke Treatment (TOAST) criteria. Safety outcomes were in-hospital intracerebral hemorrhage (ICH), symptomatic intracerebral hemorrhage (sICH) and mortality at 3-month. Efficacy outcomes were favorable functional outcome and functional independence at 3-month and neurological improvement at 24 h, 3 d and discharge. Results: In patients with large artery atherosclerosis (LAA) stroke, multivariate analyses revealed that tirofiban significantly decreased the odds of in-hospital ICH (adjusted OR=0.382, 95% CI 0.180-0.809) and tended to increase the odds of favorable functional outcome at 3-month (adjusted OR=3.050, 95% CI 0.969-9.598). By contrast, in patients with cardioembolism (CE) stroke, tirofban was not associated with lower odds of in-hospital ICH and higher odds of favorable functional outcome at 3-month (adjusted P>0.05 each), however, the association between tirofiban treatment and lower odds of neurological improvement at 24h and 3d were significant (adjusted OR<0.05 each). Conclusions: Tirofiban combined with MT appears to be safe and effective in LAA patients, but has no beneficial effect on CE patients.